Peningkatan Proses dan Hasil Belajar IPAS Menggunakan Model Accelerated Learning Berbantu Media Roda Berputar - Mella Safitri; Subhanadri Subhanadri; Randi Eka Putra (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to improve the learning process and outcomes in the subject of Natural and Social Sciences (IPAS) through the implementation of the Accelerated Learning model assisted by a spinning wheel media for fifth-grade students at SD Negeri 36/VI Rantau Panjang. The research method employed was Classroom Action Research (CAR), conducted in two cycles consisting of planning, implementation, observation, and reflection stages. Data collection techniques included observation to measure the quality of the learning process and tests to assess student learning outcomes. The results showed a significant increase in student engagement during the learning process and improvement in learning outcomes. The quality of the learning process improved from the “good” category in the first cycle to “very good” in the second cycle. Additionally, the percentage of student learning mastery increased from 55% in the initial condition to 90% at the end of the second cycle. These findings indicate that the Accelerated Learning model with the spinning wheel media is effective in creating an interactive and enjoyable learning environment, as well as enhancing student achievement. Therefore, this model is recommended for broader implementation in elementary school learning.